Enterococcus mediterraneensis sp. nov., a new bacterium isolated from the stool of a 39-year-old Pygmy. (November 2019) - Takakura, T.; Francis, R.; Anani, H.; Bilen, M.; Raoult, D.; Bou Khalil, J.Y.
Abstract: Enterococcus mediterraneensis strain Marseille-P4358 T (= CSURP4358 T ) is a new species isolated from the stool of a 39-year-old male Pygmy from the Democratic Republic of Congo.